ANALISIS KESELAMATAN KERJA PADA PENGOPERASIAN ALAT TANGKAP PURSE SEINE - Tyas Dita; Suci Asrina Ikhsan Ikhsan; Imam; Yaser; Putra (Universitas Mataram, 2024)
Occupational safety at sea does not only depend on the vessel, crew and equipment, but also on the readiness of the equipment to be used any time before departing and during the operation of vessel. The aims of research are are identifying activities and potential risks of work accidents using job safety analysis on purse seine vessels, and analyzing the value of the hazard level in fishing activities using risk assessment. The methods used in research are survey methods, interviews and documentation. Data analyze using job safety analyze, risk assessment with qualitative descriptive method. The result of research described that activities on board the purse seine are divided into several activities, they are preparation, operations which include setting, hauling and handling of fish. Analysis of fishing work activities on purse seine vessels focus in the study of fishing operations and handling of catches. The average value of the hazard level during the preparation process is medium, the hazard level during setting and hauling is low and medium, then when handling the hazard level is medium.